Strategies for developing creative thinking in the digital era through procreamath projects: Synergy of e-worksheets and project-based learning - Anggie Yudistira Aditya; Lukmanul Hakim (CV. FOUNDAE, 2025)
Background: Creative thinking is a crucial skill in mathematics education, particularly in understanding geometric concepts such as flat side space nets. However, conventional learning resources often lack the capacity to stimulate such thinking effectively. Aims: This study aims to develop an e-worksheet based on Project-Based Learning (PjBL) to enhance students' creative thinking skills in a geometry course, focusing on flat side space nets. Methods: The development process follows the ADDIE model, consisting of analysis, design, development, implementation, and evaluation phases. The e-worksheet was created using digital design tools to ensure interactive and visually engaging content. Validation was conducted by subject matter and media experts, while practicality was assessed through student feedback. Effectiveness was evaluated based on the improvement of students’ creative thinking skills. Result: The validation results indicate that the e-worksheet meets the criteria for content, visual design, and alignment with the PjBL approach. Students responded positively to the e-worksheet’s usability, clarity, and role in supporting conceptual exploration. Learning outcomes showed an increase in creative thinking, particularly in fluency and originality. However, lower achievement in flexibility and elaboration suggests the need for further instructional focus on these indicators. Conclusion: The PjBL-based e-worksheet is valid, practical, and effective in enhancing creative thinking skills and is feasible for use as an alternative mathematics learning resource. Future development should emphasize activities that strengthen flexibility and elaboration aspects of creative thinking.